Dividend Policy in Mainland China and the US: A Study on Non-Financial Listed Companies - Boo, Hooi-Laing; Tan, Bee Wah (UUM Press, 2025)
This paper aims to assess the common characteristics of dividend payers and non-payers in both China and the US, as well as the stability of dividend policies in each respective nation. The study addresses issues related to catering theory, signal theory, smoothing assumptions, and Fama-French hypotheses. Our analysis covers 509 non-financial firms during the period 2006-2016, comprising 419 firms from the US and 90 firms from China. The multinomial regression reveals that past dividend payouts are critical in explaining dividend policy in both the US and China. Firms that have consistently paid higher dividends in the preceding year are more likely to opt for dividend increases rather than omitting dividends, thus aligning with the dividend smoothing hypothesis. Additionally, firm size and stock market performance were found to be significantly influencing dividend payouts across different categories in both the US and China. However, US firms primarily drove dividend payouts through profitability and the dividend premium, while firm size and leverage heavily influenced Chinese dividends. Interestingly, Chinese firms appear to practice a less sticky dividend policy than US firms, implying that the role played by dividend policy in signalling and catering theories in China is less significant than in the US